Respuesta :
Answer: [tex]h(x)=-4x^2-6x+6[/tex]
Step-by-step explanation:
To find the function h(x), you need to subtract the function [tex]f(x)=8x^2-2x+3[/tex] and the function [tex]g(x)=12x^2+4x-3[/tex].
[tex]h(x)=f(x)-g(x)\\h(x)=8x^2-2x+3-(12x^2+4x-3)[/tex]
Distribute the negative sign:
[tex]h(x)=8x^2-2x+3-12x^2-4x+3[/tex]
Now you can add the like terms:
[tex]h(x)=-4x^2-6x+6[/tex]
Therefore, you get that the function h(x) is:
[tex]h(x)=-4x^2-6x+6[/tex]
Answer:
h(x) = - 4x² - 6x + 6
Step-by-step explanation:
It is given that,
f(x) = 8x² - 2x + 3 and
g(x) = 12x² + 4x - 3
To find h(x)
h(x) = f(x) - g(x)
h(x) = ( 8x² - 2x + 3) - (12x² + 4x - 3)
= 8x² - 2x + 3 - 12x² - 4x + 3
= 8x² - 12x² - 2x - 4x + 3 + 3
= - 4x² - 6x + 6
Therefore h(x) = - 4x² - 6x + 6